C–C Bond formation catalyzed by natural gelatin and collagen proteins - Kühbeck, Dennis; Bijayi Dhar, Basab; Schön, Eva-Maria; Cativiela, Carlos; Gotor-Fernández, Vicente; Díaz Díaz, David (Beilstein Journal of Organic Chemistry, 2013)
The activity of gelatin and collagen proteins towards C–C bond formation via Henry (nitroaldol) reaction between aldehydes and nitroalkanes is demonstrated for the first time. Among other variables, protein source, physical state and chemical modification influence product yield and kinetics, affording the nitroaldol products in both aqueous and organic media under mild conditions. Significantly, the scale-up of the process between 4-nitrobenzaldehyde and nitromethane is successfully achieved at 1 g scale and in good yield. A comparative kinetic study with other biocatalysts shows an increase of the first-order rate constant in the order chitosan < gelatin < bovine serum albumin (BSA) < collagen. The results of this study indicate that simple edible gelatin can promote C–C bond forming reactions under physiological conditions, which may have important implications from a metabolic perspective.
Keywords: biocatalysis; carbon–carbon bond formation; gelatin; Henry reaction; protein